Real‐world evidence on adherence, persistence, switching and dose escalation with biologics in adult inflammatory bowel disease in the United States: A systematic review. (14th March 2019) - Khan, Shahnaz; Rupniewska, Ewa; Neighbors, Mackenzie; Singer, David; Chiarappa, Joseph; Obando, Camilo
Summary: What is known and objective: The application of biologics to treat inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis, is well established. Our aim was to characterize the most recent five years of data on rates of adherence, persistence, switching and dose escalations with biologics used to treat IBD in the United States. Methods: We systematically reviewed electronic databases MEDLINE, MEDLINE In‐Process, EMBASE and Cochrane Library for 2012‐2017 as well as conference proceedings for 2016‐2017 published in English. Results and discussion: Of 449 records identified, 41 met all screening criteria. Published studies varied greatly in methodology, data sources, population studied, follow‐up time and endpoint definitions, preventing meaningful comparisons across studies. Based on studies using a medication possession rate threshold of <80% or <86%, 38%‐77% of patients were found non‐adherent to biologics. Discontinuation within the first 3 months occurred in 0%‐25% of patients in six studies; 7%‐65% discontinued by 12 months in 13 studies. Among all patients who initiated an index biologic, the switch rate to another biologic ranged from 4.5% to 20% in 6 studies. Dose escalations were reported in only four studies; 8%‐35% of patients had their dose escalated within the first year of therapy. What is new and conclusion: This study demonstrates variability in study design and methodology to assess adherence, persistence, switching and dose escalation with biologics among adults with IBD in the United States. Our findings suggest that real‐world biologic use may be suboptimal and indicate new therapies and/or additional patient support may be needed. Abstract : In a systematic literature review, a considerable proportion of patients with inflammatory bowel disease were found to discontinue biologic therapy (0%‐25% of patients discontinued within the first 3 months of starting of an index biologic, which increased to 7%‐65% at 12 months). Variability in studies prevents direct comparison by prior exposure to biologics and by indication.